Potential diagnostic of lymph node metastasis and prognostic values of TM4SFs in papillary thyroid carcinoma patients - Wang, Kun; Li, Haomin; Zhao, Junyu; Yao, Jinming; Lu, Yiran; Dong, Jianjun; Bai, Jie; Liao, Lin (Frontiers in Cell and Developmental Biology, 2022)
Background:Although the prognosis of papillary thyroid carcinoma (PTC) is relatively good,it causes around 41,000 deaths per year,which is likely related to recurrence and metastasis. Lymph node metastasis (LNM) is an important indicator of PTC recurrence and transmembrane 4 superfamily (TM4SF) proteins regulate metastasis by modulating cell adhesion,migration,tissue differentiation,and tumor invasion.However, the diagnostic and prognostic values of TM4SF in PTC remain unclear.Methods:This study aimed to identify TM4SFs with predictive value for LNM and prognostic value in PTC using bioinformatic analysis.We screened the differentially expressed genes(DEGs)of the TM4SFs in PTC using TCGA data,constructed a PPI network using STRING,and evaluated the predictive role of TM4SF1 in LNM via a binary logistic regression analysis and ROC curve.We assessed the association between TM4SF1 expression and DNA methylation,and determined the functional and mechanistic role of TM4SF1 in promoting LNM via GSEA,KEGG,and GO.We estimated the relationship between each TM4SFs and overall survival (OS,estimated by Kaplan–Meier analysis) in patients with PTC and established a predictive model of prognostic indicators using a LASSO penalized Cox analysis to identify hub genes.Finally, we explored the correlation between TM4SFs and TMB/MSI.Results:We identified 21 DEGs from the 41 TM4SFs between N0 and N1 patients,with TM4SF1,TM4SF4,UPK1B and CD151 being highly expressed in the N1 group; several DEGs were observed in the TNM,T and N cancer stages.The “integrins and other cell-surface receptors” pathway was the most significantly enriched functional category related to LNM and TM4SFs.TM4SF1 was identified as an indicator of LNM (AUC=0.702).High levels of TM4SF1 might be related to Wnt/β-catenin pathway and epithelial–mesenchymal transition (EMT) process in PTC. The higher expression of TM4SF1 was also related to DNA promoter hypomethylation. CD9, TM4SF4, TSPAN2,and TSPAN16 were associated with OS in PTC patients and TSPAN2 has great potential to become a prognostic marker of PTC progression.For the prognostic model,the riskscore=(-0.0058)*CD82+(-0.4994)*+(0.1584)*TSPAN11+(1.7597)*TSPAN19+(0.2694)*TSPAN2(lambda.min=0.0149).The AUCs for 3-year,5-year,and 10-year OS were 0.81,0.851 and 0.804.TSPAN18,TSPAN31 and TSPAN32 were associated with both TMB and MSI in PTC patients. Conclusions:Our findings identified TM4SF1 as a potential diagnostic marker of LNM and TSPAN2 as a prognostic factor for patients with PTC.Our study provides a novel strategy to assess prognosis and predict effective treatments in PTC.